Effect of Laser and Conventional Office Bleaching and Polishing on the Color Change of Stained Nanohybrid and Microhybrid Composite Resin - Shakiba Farahani; Taraneh Faghihi; Ladan Ranjbar Omrani; Nasim Chiniforush; Elham Ahmadi; Mandana Karimi; Mahdi Abbasi (International Journal of Dentistry)
Aim. The present study investigated the effects of laser and conventional in-office bleaching, and polishing on the color of stained composite resin. Materials and Methods. A microhybrid composite (Clearfil AP-X) and a nanohybrid composite (Grandio) were selected. Twenty-four discs (2 × 10 mm) for each composite were prepared. The samples were immersed in coffee solution (25 g of coffee in 250 mL water) for seven days. Then the samples were divided into three groups (n = 8) and the stains were removed using bleaching (with Opalescence Xtra Boost), diode laser irradiation with Heydent material and a Sof-Lex polishing kit. The L ∗a ∗b ∗ color parameters were determined using a spectrophotometer before and after immersion and after stain removal procedures, and the overall color changes (ΔE) were calculated. The data were analyzed with two-way analysis of variance. Results. In the Clearfil composite resin group, the mean ΔE compared to the baseline using in-office bleaching, laser irradiation, and Sof-Lex polishing kit were 3.31, 3.35, and 4.93, respectively. These values with the Grandio composite resin were 3.31, 6.35, and 4.57, respectively. The highest capacity to remove stains was related to the conventional in-office bleaching method. Grandio composite resin underwent more color changes than Clearfil composite resin significantly (P-value < 0.05). Conclusion. Both composite resins exhibited color changes after immersion in the discoloring solution. However, after staining-removing procedures, the ΔE values decreased. Decreases in the ΔE values were not sufficient to restore the color to that before immersion in the discoloring solution with any stain-removing methods.